Pengaruh Hatha Yoga Terhadap Kualitas Tidur Ibu Hamil Trimester III - Mirah, Ida Ayu; Widiastini, Luh Putu; Adhiestiani, Ni Made Egar (Jurnal Kebidanan Malakbi, 2025)
Pregnancy-related psychological changes might lead to sleep difficulties. Sleep disturbances are common among pregnant women in Indonesia, accounting for approximately 64% of the cases. Hatha yoga can help pregnant women overcome their sleep difficulties. The aim of this study was to determine the effect of hatha yoga on the sleep quality of the third trimester of pregnant women. The research design used Quasy Experimental with non-equivalent control groups. Purposive sampling was used to identify 44 pregnant women in their third trimester, with 24 in the intervention group and 24 in the control group. Data collection used the Pittsburgh Sleep Quality Index (PSQI) questionnaire, data analysis consisted of descriptive and comparative analysis. The study's findings revealed that both the control and treatment groups had poor sleep quality prior to the intervention. After receiving the intervention, the treatment group's average sleep quality was good, but the control group's average sleep quality was low. The Mann Whitney Test results indicated that Zcount = 5.649 > Ztabel = 1.96, with a P value of 0.000 < Î±0.05. These findings demonstrated that hatha yoga has an impact on the sleep quality of the third trimester of pregnant women. It can be inferred that hatha yoga helps to calm the body and relieve tension. Reduced muscle tone will lead to improved sleep quality. Health facilities are advised to employ hatha yoga as an intervention to address sleep disturbances in pregnant women, hence improving sleep quality